APPLE TREE DEVELOPMENT AND INTENSIFICATION OF THE BREEDING PROCESS - E. N. Sedov (Вавиловский журнал генетики и селекции)
Research of apple tree development features in connection with breeding acceleration has been conducted at the Institute of Horticultural Breeding for over 50 years. Age-related variation in trunk length is recorded even in 24 to 34-year apple seedlings. Plants grown from cuttings of seedling root shoots, as well as plants obtained from roots, usually start fruit bearing 1–3 years later than those grown from cuttings from the upper part of the crown of the same seedlings. Late fruit bearing of apple seedlings is associated with their long juvenile period. In connection with the discovered features of apple tree development, we consider opportunities of breeding acceleration and intensification by means of combination of breeding stages, agricultural methods, multiple screenings against infectious and provocative backgrounds, grafting of 2-year seedlings on 3–6-year skeletogenous trees, study of hybrid seedlings in different geographical areas, utilization of correlations of anatomical, physiological and morphological characters of young seedlings with their commercially valuable properties in adulthood, and application of molecular methods.